PPU Announcements - حسونة, روان; معيوي, ايمان; فنشه, ميساء (جامعة بوليتكنك فلسطين - تكتنولوجيا المعلومات)
The team designed a website and an application for smarts phones. the application aims to help the university and the students to reach and get to all the advertisements in an easy way. The secretary can make and add advertisements to general advertisements or depending on the major. The teacher through the site can create its own account after activation by the secretary, you can add its own courses. on the other hand the students through the smart phone application can make their own account and pick their major to get to their courses to stay tuned to the latest advertisements by getting notifications on their mobile phones.
CD , no of pages 63 , تكنولوجيا المعلومات 3/2016
Keywords: Announcements